3 D Interlayer Nanohybrids Composed of Sulfamic‐Acid‐Doped PEdot Grown on Expanded Graphite for High‐Performance Supercapacitors. Issue 2 (21st September 2015) - Kan, Kan; Wang, Lei; Yu, Peng; Zhou, Wei; Wang, Ruihong; Lin, Yufei; Shi, Keying; Fu, Honggang
Abstract: Sulfamic acid (SFA)‐doped poly(3, 4‐ethylenedioxythiophene) (PEdot) grown on expanded graphite (EG) nanohybrids (S‐PEdot/EG) were synthesized by surfactant‐free in situ chemical oxidative polymerization. The 3D hierarchical structure S‐PEdot/EG with homogenous ridgelike surface morphology was achieved by intercalating 3, 4‐ethylenedioxythiophene monomers between the interlayers of EG using a vacuum‐assisted method. The composition of the nanohybrids and the π–π interaction between the EG and PEdot molecules were characterized by using Raman spectroscopy, thermogravimetric analysis, and X‐ray photoelectron spectroscopy. The nanohybrid with an EG content of 10 % exhibited excellent capacitive performance with a high capacitance of 139.6 F g −1 at 1.0 A g −1 in 1 m LiClO4 electrolyte. In the two‐electrode symmetric supercapacitors, the device performed with a high energy density of 6.83 W h kg −1 at the power density of 146 W kg −1, and retained high stability during the charge–discharge process. The excellent performance can be attributed to the 3D hierarchical structure, the π–π interaction between EG and PEdot molecules, and the doped SFA as an immobilized counter‐ion. This cost‐effective and simple method used to fabricate 3D S‐PEdot/EG nanohybrids is promising for the generation of electrode materials for high‐performance supercapacitors. Abstract : Space to grow : Sulfamic acid (SFA)‐doped PEdot/expanded graphite (EG) interlayered nanohybrids (S‐PEdot/EG), with a 3D hierarchical structure, were synthesized by in situ chemical oxidative polymerization. The S‐PEdot/EG nanohybrids exhibited excellent capacitive performance in neutral aqueous electrolyte, which is attributed to the synergistic effect of the 3D hierarchical structure, the π–π interaction between EG and PEdot molecules, and the immobilized SFA counter‐ion doping.